Enhancing mortar properties with crushed palm oil clinker as a partial fine aggregate replacement - Nur Farah Aziera, Jamaludin; Khairunisa, Muthusamy; Mohamad Shahirudin, Mohd Nasir; Hilal, N. N. (Penerbit UMP, 2023)
The study investigated the feasibility of utilizing crushed palm oil clinker, a byproduct of the palm oil industry, as a partial substitute for fine aggregate in mortar. This initiative aimed to mitigate the environmental issues arising from sand mining and excessive disposal of palm oil clinker in landfills. Five different replacement percentages (0%, 10%, 20%, 30%, and 40%) were tested, with all specimens undergoing water curing. The research outcomes revealed significant effects on mortar properties. As the proportion of crushed palm oil clinker increased, the flowability of the mortar diminished. Nevertheless, incorporating 10% crushed palm oil clinker resulted in improved compressive strength. Conversely, higher replacement percentages (20%, 30%, and 40%) led to a diminishing trend in compressive strength due to an increased porous structure and weaker bonding. Additionally, when higher replacement percentages (20%, 30%, and 40%) were employed, the water absorption of the mortar increased. In summary, employing crushed palm oil clinker as a partial substitute for fine aggregate can help reduce waste disposal while conserving natural river sand resources. This approach offers a potential solution to address both environmental concerns and the need for sustainable construction materials.